Enterprise Risk Management (ERM), Biaya Modal dan Nilai Perusahaan Perbankan di Indonesia - Amika Putri; Husaini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The study aims to test the impact of the application of enterprise risk management (ERM) on the value of a company with capital cost as an intervening variable. The population in this study is a banking company listed on the Indonesian Stock Exchange during 2017-2021. Using purposive sampling methods obtained samples of 43 banks or a bank of 204 observations. The data analysis method used is regression analysis. Based on the results of the test the hypothesis shows that the application of ERM has a positive effect on the value of the company, but the implementation of the ERM does not have an effect on capital costs, nor does the cost of capital have an impact on the company's value, so that the variable of capital costs is not as a mediation of relationship of application ERM and company value.